2014
DOI: 10.5152/jaem.2014.19971
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Networking on Disaster Communication Used by the Emergency Medical and Rescue Staff - The Case of the Van Earthquake

Abstract: Objective: In this study, the effectiveness and usage of social networking services used by The Emergency Medical & Rescue Staff are discussed in the case of the Van earthquake. Results: In total, 66.5% of participants stated that they had made use of social networking services to get information about the disaster area before going there when they were assigned for duty for the case of the Van earthquake. Participants used social networking services mostly to communicate with their colleagues working at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…Nearly two-fifths of the MVAs were found to occur as two-vehicle collisions in this study. Studies published on the ambulance crashes so far have agreed that most MVAs occur in the crossroads as two-vehicle collisions whose outcomes are commonly mortal 5 8 They suggested that traffic signals be strictly heeded at crossroads and speed limits in urban settings be obeyed.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Nearly two-fifths of the MVAs were found to occur as two-vehicle collisions in this study. Studies published on the ambulance crashes so far have agreed that most MVAs occur in the crossroads as two-vehicle collisions whose outcomes are commonly mortal 5 8 They suggested that traffic signals be strictly heeded at crossroads and speed limits in urban settings be obeyed.…”
Section: Discussioncontrasting
confidence: 77%
“…Motor vehicle accidents are known to constitute the most fatal cause of WRI for the personnel staffed in EMS 5 . Ambulance MVAs cause a death toll four times greater than that of other occupations 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies: Three studies were rated with a moderate risk of bias [25][26][27] and three were rated with low risk of bias [28][29][30].…”
Section: Quality Appraisal and Data Extractionmentioning
confidence: 99%
“…Fifteen studies published between 2009 and 2021 were included in the review. Six studies had employed quantitative research methods [25][26][27][28][29][30], six had used qualitative research methods [31][32][33][34][35][36][37] and three had employed a mixed-methods approach [37][38][39]. The studies included in this review had been conducted in ten countries: Japan [25]; China [29,33], Iran [35,37]; Romania [26]; the US [31,32,35]; Canada [30,37]; the Republic of Ireland [28]; Turkey [27]; Australia [38] and the UK [39].…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%